Profiling CEFR-basic readers at primary schools through their eye movement behaviours - Warid Mihat; Hazita Azman; Nurjanah Mohd Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study profiles CEFR-basic readers in Malaysia by examining their eye movements and fixations during reading comprehension tasks in response to the studies conducted by Cambridge Assessment in Malaysia in 2013 and 2018. To this end, forty 12-year-old school pupils at A1/A2 reading proficiency level were observed using Tobii Pro Glasses 100hz. The participants were asked to read three texts and answer ten multiple-choice questions. Data were transformed into statistics and gaze plots. The results of the experiment indicate that basic readers in this study have an average first pass duration (FPD) of 0.50-0.59 seconds and an average second pass duration (SPD) of 0.76-0.81 seconds. This study also found four pejorative behaviours that can impede the process of reading: 1) rereading at micro level, 2) limited processing capacity for sentences of more than 14 words, 3) negative skipping and, 4) desegmentation. Through these behaviours, this study highlights the importance of improving the readers’ reading skills to improve the quality of their SPD as it is related to the ability to process and integrate the various subprocesses involved in reading. While this study suggests the need for further replication in diverse reading environments, it also provides valuable insights into the current reading proficiency of Year 6 pupils in their second language.